Derivation of Mathematical Equations to Calculate the Geographical Coordinates of Unknown Position Situated at a Distance from the Observer Position Using GPS Data - Hatem, Amaal J.; Naji, Taghreed A.; Ne'ma, Ali A.; Jar Allah, Naz T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This research introduced the derivation of mathematical equations to calculate the Cartesian and geographical coordinates of a site situated at a far distance from the observer position by using GPS data. The geographical coordinates (Ï•obs., Î» obs., hobs.) for observer position were transformed to Cartesian coordinates (X obs., Y obs., Z obs.) of observer position itself. Then the Cartesian coordinates of unknown position mathematically were calculated from these calculated equations, and its transformed to geographical coordinates of (Ï•unk., Î»unk.) position.